2014
DOI: 10.1074/jbc.m113.527150
|View full text |Cite
|
Sign up to set email alerts
|

FGF-23 Is a Negative Regulator of Prenatal and Postnatal Erythropoiesis

Abstract: Background: FGF-23, a bone-derived hormone, regulates phosphate and vitamin D in the kidney. Results: Genetic and pharmacological manipulations of FGF-23 alter erythropoiesis and HSC frequency both in young adult age and embryonically. Conclusion: Fgf-23 regulates erythropoiesis through Epo and independent of vitamin D. Significance: These findings provide a new target for treating blood disorders associated with bone and renal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 46 publications
(59 reference statements)
5
127
0
Order By: Relevance
“…Alternative hypothesis have included phosphorusinduced accumulation of polyamine toxins [19] , increased production of diphosphoglycerate and adenosine triphosphate, leading to rightward shift in the oxygen-hemoglobin dissociation curve and subsequent downregulation of erythropoietin receptors [15] and increased levels of fibroblast growth factor (FGF-23) [18,19] . With regard to the latter, recent investigations on murine models have shown that genetic inactivation of either FGF-23 or klotho, an essential cofactor in FGF-23 signaling pathways, entails a substantial increase in erythropoietic activity in all hematopoietic tissues, a greater expression of erythropoietin mRNA in bone marrow, liver and kidney, and an increase in circulating erythropoietin levels [35,36] . With respect to a possible relationship between serum calcium and anemia, it has been practically unnoticed until now.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative hypothesis have included phosphorusinduced accumulation of polyamine toxins [19] , increased production of diphosphoglycerate and adenosine triphosphate, leading to rightward shift in the oxygen-hemoglobin dissociation curve and subsequent downregulation of erythropoietin receptors [15] and increased levels of fibroblast growth factor (FGF-23) [18,19] . With regard to the latter, recent investigations on murine models have shown that genetic inactivation of either FGF-23 or klotho, an essential cofactor in FGF-23 signaling pathways, entails a substantial increase in erythropoietic activity in all hematopoietic tissues, a greater expression of erythropoietin mRNA in bone marrow, liver and kidney, and an increase in circulating erythropoietin levels [35,36] . With respect to a possible relationship between serum calcium and anemia, it has been practically unnoticed until now.…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 signaling is involved in immune regulation through impairment of macrophage and neutrophil function [27]. Preclinical data suggest a novel role for elevated FGF23 in hematopoiesis through impairment of erythropoiesis in bone marrow cells [28]. Deletion of FGF23 in wild-type mice resulted in increased erythropoiesis in bone marrow independent of vitamin D, and exogenous FGF23 administration resulted in a rapid decrease in erythropoiesis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data suggest a novel role for elevated FGF23 in hematopoiesis through impairment of erythropoiesis in bone marrow cells [28]. Deletion of FGF23 in wild-type mice resulted in increased erythropoiesis in bone marrow independent of vitamin D, and exogenous FGF23 administration resulted in a rapid decrease in erythropoiesis [28]. FGF23 levels in the latter studies were parallel to levels detected in murine models with CKD, supporting the hypothesis that elevation of FGF23 observed in CKD may contribute to the development of anemia [29].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, 1,25(OH) 2 D 3 levels in bone marrow are a magnitude higher in comparison to their levels in plasma [22]. Animal experiments have revealed that FGF23 deficiency leads to hyperphosphatemia paralleled with increased levels of vitamin D and enhanced prenatal and postnatal erythropoiesis [23]. However, enhanced erythropoiesis in those mice was shown to be independent of increased 1,25(OH) 2 D 3 levels [23].…”
Section: Introductionmentioning
confidence: 99%